Mechanical System Approaches Limit of Technical Feasibility: Tailor‐made positioning solution for analytical methods performed on a beamline. Issue 1 (18th February 2016) - Schulze, Birgit
Abstract: Nowadays, X‐ray and tomographic methods help detect very fine structures inside objects. For spatial resolutions down to 100 nanometers, diffractive X‐ray optics are available today. However, various challenges have to be overcome to obtain a three‐dimensional image with volume resolution in this range. It is a major challenge to achieve the extremely high mechanical accuracy and stability required for the alignment of the optics and samples in the X‐ray beam and for the entire experimental setup. Even minute changes in temperature or vibrations could degrade the desired resolution. This is why the improvement of the X‐ray optics must always go hand in hand with the mechanical perfection of the entire setup. If specialists work closely together, considerable progress can be made as shown by the example described below.